2014
DOI: 10.3389/fpsyg.2014.01086
|View full text |Cite
|
Sign up to set email alerts
|

Cold-hearted or cool-headed: physical coldness promotes utilitarian moral judgment

Abstract: In the current study, we examine the effect of physical coldness on personal moral dilemma judgment. Previous studies have indicated that utilitarian moral judgment—sacrificing a few people to achieve the greater good for others—was facilitated when: (1) participants suppressed an initial emotional response and deliberately thought about the utility of outcomes; (2) participants had a high-level construal mindset and focused on abstract goals (e.g., save many); or (3) there was a decreasing emotional response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 39 publications
1
17
1
Order By: Relevance
“… Nakamura et al (2014) investigated the effect of haptic temperature on moral judgments using the moral dilemma task. In this task, the offered dilemmas reflect situations in which the subject can save a larger number of lives by sacrificing one person’s life.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“… Nakamura et al (2014) investigated the effect of haptic temperature on moral judgments using the moral dilemma task. In this task, the offered dilemmas reflect situations in which the subject can save a larger number of lives by sacrificing one person’s life.…”
Section: Methodsmentioning
confidence: 99%
“…It has also been reported that a hot temperature promotes prosocial behavior ( Williams and Bargh, 2008 ) and enhances cooperative behavior in prisoner’s dilemma tasks ( Storey and Workman, 2013 ). On the other hand, research has shown that a cold temperature induces lower investment in trust games ( Kang et al, 2011 ), tougher inferences of suspect guilt ( Gockel et al, 2014 ), and more utilitarian judgments in moral dilemma tasks ( Nakamura et al, 2014 ). These studies suggested that temperature has a considerable impact on real-world behavior beyond simple task performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Originally developed to measure individual differences in identification level across action domains (i.e., level of personal agency), the BIF (Vallacher & Wegner, 1989) is widely regarded as a useful measure of differences in construal and abstraction level and is frequently employed in research on various aspects of cognition and behavior (e.g., Dar & Katz, 2005; Smith & Trope, 2006). The BIF has so far been translated and adapted into several languages, including Chinese (Gu & Tse, 2018), French (Brown, 2014), Dutch (Smith & Trope, 2006), Japanese (Nakamura, Ito, Honma, Mori, & Kawaguchi, 2014), and Turkish (Yetişer, 2014), but has not yet been validated in Polish. In fact, although action identification theory was introduced over three decades ago (Wegner & Vallacher, 1986), the local literature has largely overlooked it.…”
Section: Conclusion and Limitationsmentioning
confidence: 99%
“…For instance, people primed with coldness are more likely to choose a gift for themselves than for others. Many subsequent studies then focused on the connection of physical and social warmth, and provided hints for its bi-directionality ( IJzerman and Semin, 2009 ; Hu et al, 2016 ), while more recent studies have also taken coldness (rather than warmth) into consideration ( Nakamura et al, 2014 ; Willemse et al, 2015 ; Zhong and Leonardelli, 2015 ). The expressions ‘ keeping it cool’ or ‘ playing it cool’ are used in our everyday life to express self-control and non-emotional behavior.…”
Section: Embodiment and Coldness Primingmentioning
confidence: 99%